The role of the macrophage polarization type in the pathogenesis of endometrioid disease - Y. А. Orlova; A. М. Gromova; O. Ye. Akimov; O. М. Ketova (Zaporožskij Medicinskij Žurnal)
Endometriosis today occupies one of the leading places in the structure of general gynecological pathology. Theories of the onset and progression of this disease are controversial. One of the most widespread theories is the assumption that endometriosis is a disease of macrophages. The question of which the macrophage phenotype, M1 or M2, is the leading one, however, remains controversial.